Analysis of Emotional Intelligence, Environment and Discipline on Student Learning Achievement - Yunita Yunita; Indasah Indasah; Siti Farida (Journal for Quality in Public Health, 2019)
Education is very important for improving the quality of human resources. Associated with the world of education, to create high quality and high achievers. Factors that can influence learning include emotional intelligence, the environment and the discipline in which individuals carry out certain activities so that they can achieve maximum performance. The purpose of the study was to analyze the effect of emotional intelligence , environment and discipline on student achievement in Health Vocational School Visi Global in Banyuwangi Regency . In this study, the research design used was cross sectional . The study population was all students of Banyuwangi Health Vocational School Visi Global 117 students and a sample of 91 people using stratified random sampling . Collecting data using a questionnaire sheet and then analyzed using multiple linear regression test. The results showed that a significant probability of F value of 0.000 <0.05 means that there is an influence of emotional intelligence (X1), learning environment (X2) and learning discipline (X3) simultaneously or partially have a significant effect on learning achievement (Y) in Vocational School in Visi Global Banyuwangi Regency. Based on the results of this study, it needs to be at the level of things that affect learning achievement by providing facilities and infrastructure that support learning that is not yet available and create a more comfortable learning environment.